Wilde Writings : Contextual Conditions - Bristow, Joseph (Book collections on Project MUSE., 2003)
"Wilde Writings brings together research by established and emerging scholars, some of whom draw on unpublished archival material, and all of whom have something new and enlightening to say about Wilde. The collection provides fresh insights into critical debates about Wilde and effeminacy, masochism, and Christian theology, and also draws attention to significant problems in the textual editing of his writings, his debt to the 'aesthetic' fiction of the novelist Ouida, and the popularity of his drama in twentieth-century China."--Jacket.